Nationalism and internationalism in imperial Japan : autonomy, Asian brotherhood, or world citizenship? - Stegewerns, Dick (RoutledgeCurzon, 2003)
Throughout the history of modern Japan there has been a continuous struggle to create an integrated conception of how a politically and/or culturally autonomous Japan might relate to a pluralistic and interactive world. The aim of this study is to scrutinise nationalist and internationalist rhetoric by means of comparatively constant factors such as personal views of humanity, civilisation, progress, the nation and the outside world, and thus to develop new approaches towards the question of the relationship between Japanese nationalism and internationalism. This project brings together a.